GAME ONLINE (QUIZIZZ) SEBAGAI TANTANGAN BARU DALAM MEMBANGUN KARAKTER DISIPLIN SISWA KELAS III MADRASAH IBTIDAIYAH - Faizatul Widat; Isyatur Rodiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the influence of online gaming habits on student discipline and the use of Quizizz-based learning media in improving the discipline of grade III B students of Madrasah Ibtidaiyah Al-Islamiyah. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study were 21 students of class III B and class teachers. The results of the study showed that some students have the habit of playing online games with quite high intensity which has an impact on declining learning discipline, such as lack of focus, delay in collecting assignments, and low learning responsibility. On the other hand, the use of Quizizz as a learning medium has a positive impact on increasing student engagement and discipline. Learning becomes more interactive, fun, and able to encourage students to be more punctual and responsible in completing tasks. Quizizz features such as time limits, scoring systems, and rankings also play a role in shaping students' discipline attitudes. Thus, Quizizz can be an alternative innovative learning media that supports the formation of student discipline character in elementary school. However, the effectiveness of the use of this media is greatly influenced by the role of teachers, parents, and the conditions of the learning environment so that it cannot be generalized to all educational institutions.